Proteopathic tau primes and activates interleukin-1β via myeloid-cell-specific MyD88- and NLRP3-ASC-inflammasome pathway - Shanya Jiang (Cell Reports, 2021)
Summary: Pathological hyperphosphorylation and aggregation of tau (pTau) and neuroinflammation, driven by interleukin-1β (IL-1β), are the major hallmarks of tauopathies. Here, we show that pTau primes and activates IL-1β. First, RNA-sequence analysis suggests paired-helical filaments (PHFs) from human tauopathy brain primes nuclear factor κB (NF-κB), chemokine, and IL-1β signaling clusters in human primary microglia. Treating microglia with pTau-containing neuronal media, exosomes, or PHFs causes IL-1β activation, which is NLRP3, ASC, and caspase-1 dependent. Suppression of pTau or ASC reduces tau pathology and inflammasome activation in rTg4510 and hTau mice, respectively. Although the deletion of MyD88 prevents both IL-1β expression and activation in the hTau mouse model of tauopathy, ASC deficiency in myeloid cells reduces pTau-induced IL-1β activation and improves cognitive function in hTau mice. Finally, pTau burden co-exists with elevated IL-1β and ASC in autopsy brains of human tauopathies. Together, our results suggest pTau activates IL-1β via MyD88- and NLRP3-ASC-dependent pathways in myeloid cells, including microglia.